Individual Choice and State-Led Nationalist Mobilization in China: Self-interested Patriots - Zha, Wen (Springer, 2015)
This book presents a comparative historical analysis of state-led nationalist movements in Chinese history, which counters current claims that popular nationalism in present-day China is strong enough to sustain costly expansionist wars. Popular nationalism in China has been on the rise since the early 1990s to the concern of many observers. Some have even asked whether China will become another Germany. A comparative historical analysis of pre-war and wartime nationalist mobilization helps us better understand how individuals formulate their opinions under extreme conditions. It concludes that the public's weak perception of foreign threats, taken together with pro-minority domestic institutions, may significantly undermine the state’s efforts at nationalist mobilization and thus limit its capability to pursue external expansion or other strategic goals.